Mapping the Galactic halo with main-sequence and RR Lyrae stars - Sesar B. (EPJ Web of Conferences, 2012)
We present an analysis of Galactic halo structure, substructure, and metallicity traced by main-sequence and RR Lyrae stars selected from the SDSS stripe 82 and CFHT Legacy Survey data sets. The main result of the study based on SDSS stripe 82 data is a 2D map of the Galactic halo that reaches distances of 100 kpc and traces previously known and new halo substructures, such as the Sagittarius and Pisces tidal streams. We present strong direct evidence, based on both RR Lyrae and main-sequence stars, that the halo stellar number density profile significantly steepens beyond 30 kpc from the Galactic center. The steepening of the density profile beyond 30 kpc is also evident in the distribution of main-sequence stars observed by the CFHT Legacy Survey along four Galactic lines of sight. In the two CFHT sightlines where we do not detect significant substructure, the median metallicity is found to be independent of distance within systematic uncertainties ([Fe∕H] ~ −1.5 ± 0.1 dex within 30 kpc of the Galactic Center).